Hair hormones in male youth with internet gaming disorder. (21st April 2019) - Koenig, Julian; Thaler, Veronica; Parzer, Peter; Resch, Franz; Kaess, Michael
Abstract: Objectives: Internet gaming disorder (IGD) is associated with altered physiological reactivity to psychosocial stress. Findings from a previous study on alterations of basal hypothalamic–pituitary–adrenal (HPA) axis functioning, indexed by differences in hair hormone levels (i.e., cortisol) in IGD patients compared to matched controls, were limited by a small sample size. Methods: Following the protocol of the previous study, male patients with IGD ( n = 31) and controls ( n = 31) matched for age, educational status and smoking were recruited. Sociodemographic and clinical characteristics were assessed using structured interviews and self-reports. Hair samples were taken for the analysis of cortisol, cortisone, testosterone, progesterone, dehydroepiandrosterone (DHEA), and corticosterone. Results: Groups showed no significant differences on cortisol ( d = −0.10, 95%CI (−0.60; 0.40)), cortisone ( d = −0.10, 95%CI (−0.60; 0.40)), testosterone ( d = −0.00, 95%CI (−0.51; 0.51)), progesterone ( d = −0.46, 95%CI (−0.96; 0.05)), DHEA ( d = −0.04, 95%CI (−0.54; 0.47)) or corticosterone ( d = −0.19, 95%CI (−0.69; 0.32)). Associations between hair hormone concentrations, symptom severity and sociodemographic variables were weak and did not survive correction for multiple testing. Conclusions: Unlike other psychiatric disorders, effects of IGD and associated psychopathology on basal HPA axis functioning, indexed by hair hormone levels, are negligible. Future studies need to rule out potential effects of sex, age and long-term pathology on these findings.